Assessment of Pedestrian Walking Speed Through the Religious Occasions in Iraq (Journal of Engineering, 2019)
The design of safe pedestrian facilities usually depends on the assessment of pedestrian characteristics and behavior. In this investigation, pedestrian walking speed through the religious occasion have been monitored at three locations, Al- Kadhimiya (Imam AL-Kadim), Najaf and Karbala (Imam AL-Husain) holy shrines. Video captures of the pedestrian through their walking to the two holy shrines have been prepared and analyzed for walking speed, gender, age groups, and clothing tradition. The pedestrian sample size is 468, 501, and 447 for Al- Kadhimiya, Karbala, and Najaf respectively. When the gender is taken into consideration, it can be noted that the walking speed of male and female pedestrian is (0.97, 1.68, and 1.63) and (0.82, 1.46, and 1.48) meter/second for Al- Kadhimiya, Karbala, and Najaf respectively. When the cloth tradition is considered, female pedestrian wearing Arabic style is slower than male by 9% for Karbala and Najaf and 3% for Al- Kadhimiya. On the other hand, when age groups are considered, the elder pedestrian is slower in walking by 6% regardless of the gender and location. It was recommended that the restricted walking path at Al- Kadhimiya could be improved to control the jam density of pedestrian and increase the walking speed to its standard limit.